2020
DOI: 10.4269/ajtmh.19-0367
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Sick Children Seeking Care in the Private Health Sector in Uganda: A Cluster Randomized Trial

Abstract: The main objective of this study was to assess whether training of private health providers and community sensitization on the importance of effective prompt care seeking and the need for referral could improve treatment of sick children in the private health sector in Uganda. Private providers were trained to diagnose and treat sick children according to the integrated community case management (iCCM) guidelines. In the control arm, routine services were offered. The outcomes were seeking care within 24 hours… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Drug shop vendors expressed a desire to receive training to improve the health services they provide for the community, and trainings were an acceptable option to health officials and VHTs. While previous interventions in Uganda trained drug shop vendors on how to use and interpret RDTs [21][22][23][24][25], vendors in our study reported high levels of comfort using RDTs. Therefore, we recommend trainings focus on more nuanced aspects of RDT use, such as counseling.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Drug shop vendors expressed a desire to receive training to improve the health services they provide for the community, and trainings were an acceptable option to health officials and VHTs. While previous interventions in Uganda trained drug shop vendors on how to use and interpret RDTs [21][22][23][24][25], vendors in our study reported high levels of comfort using RDTs. Therefore, we recommend trainings focus on more nuanced aspects of RDT use, such as counseling.…”
Section: Discussionmentioning
confidence: 60%
“…Several programs in Uganda have increased the use of RDTs at drug shops, and improved the quality of malaria case management more generally, through vendor trainings, community-level demand generation activities, provision of free or subsidized RDTs, and peer supervision [21][22][23][24][25][26]. While most studies were pilot interventions focused on RDT introduction [21][22][23][24], these diagnostic tests are now commonly stocked at drug shops [27].…”
Section: Introductionmentioning
confidence: 99%
“…Inappropriate care for these common childhood infections has been described by other researchers in Uganda and other LMICs. Mbonye et al in their research among private clinics and drug shops found that children with normal respiratory rates received unnecessary antibiotics for pneumonia [44], while Kjaergaad et al found inappropriate prescription rate of antibiotics for viral upper respiratory tract infections of 23-68% in Uganda and other countries across the globe [45]. Other studies carried out in private and public health facilities in Uganda and other African countries found that 7-24% children testing positive for malaria never received the correct malaria medicine [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…The intervention improved prompt care seeking within 24 hours of onset of symptoms, included a high adherence to mRDT results, and appropriate treatment of mRDT-positive children with ACTs was high, as well as diagnosis and treatment of diarrhea and pneumonia. 11 This provides further justification to scale up iCCM in poorly planned settlements in Uganda.…”
Section: Discussionmentioning
confidence: 99%
“…Even in planned urban settlements with a well-established formal and informal private sectors, it has been shown that treatments received in these areas are often inadequate or inappropriate. 3 11 Training of accredited private sector providers to deliver iCCM remains an alternative approach that has yet to be tested—but has so far been identified as a priority for research. 2 4 …”
Section: Introductionmentioning
confidence: 99%